Global security watch : Pakistan - Hasnat, Syed Farooq (New Delhi : Pentagon Press, 2012)
In recent years Pakistan has emerged as a major security concern for the United States. The acts of terrorism that originate in Pakistan and its culture of extremism cause serious apprehension for the international community as well. Pakistan's ability to combat extremism within its borders and its policy towards Afghanistan will also play a large role in determining the success of U.S. military actions in Afghanistan. This volume will be the first to deal with a variety of emerging security issues of the country and their regional and international implications. This volume examines the issues of utmost importance for Pakistan's stability and strategic balance, and explains their significance from the global perspective. Each chapter in this book addresses specific security challenges of Pakistan, both domestic and international.
H.B
Keywords: International relations; National security; Pakistan; Political science; Strategic aspects of individual places